94 Common Social Determinants of Health as Independent Predictors of Adverse Childhood Experiences and the Derivation of a Clinical Prediction Rule: Findings from a Longitudinal Quality Improvement Study. (21st October 2022) - Carwana, Matthew; Oberg, Sara; Loock, Christine
Abstract: Background: Adverse Childhood Experiences (ACEs) are a group of early life events that lead to toxic stress and adverse adult health outcomes. Screening for ACEs can be challenging due to sensitivity and re-traumatization. There is a paucity of evidence regarding whether other social determinants of health (SDoH) might be independent predictors of an ACE score >=4. Likewise, no effective prediction rule exists for an elevated ACE score based on SDoH in children. Objectives: 1) Identify independent predictors of elevated ACE score from commonly screened SDoH. 2) Derive a clinical prediction rule based on the available data. Design/Methods: Data were drawn from a longitudinal quality improvement SDoH study in pediatric surgical clinics at a provincial children's hospital. Primary outcome of interest was an ACE score >=4. Multivariable logistic regression was utilized to identify independent predictors among other SDoH. Prediction methods and ROC analyses were completed to derive a prediction rule. Results: 515 respondents answered ACE screening; 63 (12.2%) reported >=4 ACEs. SDoH that were strong independent predictors of ACE score >=4 included poverty (OR 2.34, 95% CI 1.19-4.91), parental education (OR 2.76, 95% CI 1.17-6.54), and household income (OR 2.17, 95% CI 1.09-4.32). Housing status, Indigenous status, and disability status were not associated with elevated ACE score. A clinical prediction rule derived using four SDoH questions with a cut-off score of 1 had 96.67% sensitivity but only 21.54% specificity for an ACE score >=4 (AROC 0.75, 95% CI 0.69-0.81). Conclusion: Several adverse SDoH were identified as independent predictors of an ACE score >=4 in children. A clinical prediction rule based on SDoH screening was sensitive but poorly specific for ACE >=4. Further research is required.